Chemical liquid composition for natural ground consolidation

A urethane-based chemical composition for ground consolidation, combining an active hydrogen group-containing organic compound with a metal carboxylic acid salt catalyst and an aliphatic polyisocyanate prepolymer, addresses the challenges of slow reaction rates and environmental contamination in existing methods, achieving a high-strength, flexible, and flame-retardant consolidation body.

JP2025061835AInactive Publication Date: 2025-04-11ASAHI YUKIZAI KOGYO CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025011455
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing ground consolidation methods using aliphatic polyisocyanate compounds face issues such as slow reaction rates, leakage, water cloudiness, and foaming, leading to inadequate ground stabilization and environmental contamination.

Method used

A urethane-based chemical composition is developed, comprising liquid A with an active hydrogen group-containing organic compound having a cyclic structure and a metal carboxylic acid salt catalyst, and liquid B with an aliphatic polyisocyanate prepolymer, which together form a high-strength, flexible, and flame-retardant consolidation body with improved reaction activity and reduced environmental impact.

Benefits of technology

The composition achieves rapid curing, minimizing leakage and environmental contamination, while producing a consolidation body with high strength, flexibility, and flame retardancy, effectively addressing the limitations of previous methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061835000001
    Figure 2025061835000001
  • Figure 2025061835000002
    Figure 2025061835000002
  • Figure 2025061835000003
    Figure 2025061835000003
Patent Text Reader

Abstract

To provide urethane-based chemical liquid for natural ground consolidation, excellent in reaction activity and causing less environment pollution, and to provide an urethane-based chemical liquid composition for natural ground consolidation, capable of forming a consolidated body having high strength and excellent flexibility, and high plasticity and fire retardancy, and not initiating problems such as white turbidness and foaming when contacting water such as water leakage and sump water.SOLUTION: A chemical liquid composition for natural ground consolidation comprises A liquid containing an active hydrogen group-containing compound and a catalyst as essential components, and B liquid containing polyisocyanate as the essential component. The A liquid contains at least an active hydrogen group-containing organic compound having a cyclic structure as the active hydrogen group-containing compound, and at least a carboxylic acid metal salt as the catalyst. The B liquid contains at least an aliphatic polyisocyanate compound as the polyisocyanate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid composition for consolidating ground, and in particular to a urethane-based liquid for consolidating ground that is highly reactive and causes little environmental pollution, and that can provide a high-strength consolidated body by combining an active hydrogen group-containing organic compound having a cyclic structure with an aliphatic polyisocyanate compound. [Background technology]

[0002] Conventionally, a method of injecting an inorganic or organic grout to consolidate natural ground has been known as one of the measures employed in ground improvement applications for stabilizing and strengthening unstable bedrock or ground in natural ground, and in cavity filling applications for filling cracks and voids in artificial structures. For example, Japanese Patent Laid-Open Publication No. 4-283290 discloses, as one such grout, an injection liquid composition comprising an aqueous solution of sodium silicate (A) and a polyisocyanate composition (B) comprising a reactive diluent which does not react with polyisocyanate but is hydrolyzed by the aqueous solution of sodium silicate and reacts with the aqueous solution of sodium silicate and / or polyisocyanate. Furthermore, JP 5-78667 A discloses a two-component urethane foam resin as a bedrock consolidation liquid, which is a combination of Liquid A, whose main components are water and an alkali metal salt of silicate, and Liquid B, whose main component is an isocyanate prepolymer. Furthermore, JP 2016-175982 A proposes a two-component ground consolidation liquid consisting of Liquid A, which is prepared by blending water glass and polyol and adding water, and Liquid B, whose essential component is polyisocyanate, in which the water content in Liquid A is regulated and the water and polyol are adjusted to a specified ratio, with a dispersant further added.

[0003] As the polyisocyanate which is the main component of Liquid B in these consolidation liquids, various organic isocyanate compounds having two or more isocyanate groups in the molecule or their modified products (prepolymers) can be used. However, from the standpoint of reaction activity and the strength of the resulting solidified body, aromatic polyisocyanate compounds such as diphenylmethane diisocyanate (MDI), polymethylene polyphenylene polyisocyanate (crude MDI), polymeric MDI, tolylene diisocyanate (TDI), etc. are used in practice. In particular, when Liquid B, which is made using an aliphatic polyisocyanate compound such as hexamethylene diisocyanate or isophorone diisocyanate as the polyisocyanate component, is combined with Liquid A as described above to make a consolidation liquid, the reaction between Liquid A and Liquid B is slow, and as a result, when stopping a large amount of water leakage or spring water, some of the injected liquid flows out along with the leakage or spring water, causing problems such as clouding of the water and foaming, which have an adverse effect on the environment.In addition, the strength and flame retardancy of the solidified body formed by the reaction of Liquid A and Liquid B are insufficient, and therefore it is not capable of fully meeting the purposes of stabilizing and strengthening the ground or filling cavities. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 4-283290 [Patent Document 2] Japanese Patent Application Publication No. 5-78667 [Patent Document 3] JP 2016-175982 A Summary of the Invention [Problem to be solved by the invention]

[0005] In light of the above circumstances, the present inventors have conducted extensive research into consolidation solutions using an aliphatic polyisocyanate compound as the polyisocyanate. As a result, they have found that by combining such an aliphatic polyisocyanate compound with an active hydrogen group-containing organic compound having a cyclic structure as an active hydrogen group-containing compound, and further using at least a carboxylate metal salt as a catalyst, all of the problems that arise when using an aliphatic polyisocyanate compound as described above can be eliminated, and have thus completed the present invention.

[0006] Therefore, the problem to be solved by the present invention is to provide a urethane-based liquid ground consolidation composition which has excellent reactivity and causes little environmental pollution, and another problem is to provide a urethane-based liquid ground consolidation composition which is capable of forming a solidified body which has high strength and excellent flexibility, and has high toughness and flame retardancy, and which does not cause problems such as clouding or foaming when it comes into contact with water, such as leaking water or spring water. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention can be preferably implemented in various aspects as listed below, and each aspect described below can be adopted in any combination. It should be considered that the aspects and technical features of the present invention are not limited to those described below, but are understood based on the inventive idea grasped from the description of the entire specification.

[0008] First, a first aspect of the present invention is a liquid composition for consolidating ground comprising liquid A containing an active hydrogen group-containing compound and a catalyst as essential components, and liquid B containing a polyisocyanate as an essential component, wherein liquid A contains at least an active hydrogen group-containing organic compound having a cyclic structure as the active hydrogen group-containing compound, and contains at least a carboxylate metal salt as the catalyst, and liquid B contains at least an aliphatic polyisocyanate compound as the polyisocyanate.

[0009] In a second aspect of the present invention, the cyclic structure of the active hydrogen group-containing organic compound has an aromatic cyclic structure, an alicyclic structure, or a heterocyclic structure.

[0010] Furthermore, in a third embodiment according to the present invention, a phenol-based compound is used as the active hydrogen group-containing organic compound.

[0011] A fourth aspect of the present invention is to use a phenol resin as the active hydrogen group-containing organic compound.

[0012] In addition, in the fifth aspect of the present invention, the ratio of cyclic structures in the active hydrogen group-containing organic compound is 15 mass % or more.

[0013] In a sixth aspect of the present invention, the ratio (X / Y) of the total number of moles of active hydrogen groups in the liquid A (X) to the number of moles of isocyanate groups in the liquid B (Y) is 0.3 to 3.0.

[0014] In a seventh aspect of the present invention, the aliphatic polyisocyanate compound is a prepolymer and has a residual monomer content of less than 5 mass %.

[0015] Furthermore, in an eighth aspect of the present invention, the prepolymer of the aliphatic polyisocyanate compound is any one of an adduct, a biuret, an allophanate, and an isocyanurate derived from an aliphatic polyisocyanate compound selected from the group consisting of pentamethylene diisocyanate, hexamethylene diisocyanate, octamethylene diisocyanate, isophorone diisocyanate, and bis(isocyanatomethyl)cyclohexane.

[0016] In addition, in a ninth embodiment of the present invention, a tertiary amine is further contained as a catalyst.

[0017] Furthermore, a tenth aspect of the present invention is configured such that the liquid A and / or the liquid B further contain a flame retardant.

[0018] In an eleventh aspect of the present invention, the liquid A and the liquid B each have a viscosity of 6000 mPa·s or less at a temperature of 25°C. Effect of the Invention

[0019] According to the constitution of the liquid composition for natural ground consolidation according to the present invention, various effects as listed below can be achieved. (1) A urethane-based ground consolidation liquid that has excellent reactivity and causes little environmental pollution is provided, and the use of such a liquid makes it possible to advantageously form a solidified body that has high strength, excellent flexibility, toughness, and high flame retardancy. (2) After the chemical solution is injected into the ground, the hardening reaction begins immediately, which prevents the chemical solution from leaking into the environment and advantageously reduces the cloudiness and foaming of leaking water and spring water. (3) A metal carboxylate is used as a catalyst. By using a tertiary amine catalyst in combination with this, the reaction rate is less affected even in the presence of water, and the desired solidified body can be formed quickly, thereby advantageously enhancing its practicality. (4) By using an aliphatic polyisocyanate compound, particularly a prepolymer of an aliphatic polyisocyanate compound, as the polyisocyanate, which is an essential component of the B liquid, a strong solidified body can be advantageously formed, and pollution of the working environment at the site where the chemical solution is injected can be effectively suppressed or avoided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] In short, in the present invention, in a two-liquid type urethane liquid chemical composition consisting of liquid A and liquid B, liquid A contains an active hydrogen group-containing organic compound having a cyclic structure as the active hydrogen group-containing compound which is an essential component of liquid A, and at least a metal carboxylate as a catalyst, while liquid B contains an aliphatic polyisocyanate compound, particularly a prepolymer of an aliphatic polyisocyanate compound, as the polyisocyanate which is an essential component of liquid B. As a result, even with an aliphatic polyisocyanate compound, excellent reaction activity can be effectively achieved and a high-strength solidified body can be advantageously formed, and thus the intended object can be advantageously achieved, which is a major feature of the present invention.

[0021] In the A liquid, which is one of the two liquids constituting the liquid drug composition according to the present invention, the active hydrogen group-containing organic compound having a cyclic structure, which is an active hydrogen group-containing compound contained as one of its essential components, is an organic compound having a cyclic structure or a cyclic structure in the molecule and having an active hydrogen group such as a hydroxyl group or an amino group, and the cyclic structure can be exemplified by aromatic ring, alicyclic, heterocyclic, etc., among which aromatic ring, alicyclic, and heterocyclic compounds are preferred, aromatic ring structures are more preferred, and in particular, it is desirable to have a structure in which a hydroxyl group or an amino group is directly bonded to an aromatic ring structure.Among these, polyfunctional compounds having two or more functional groups are more desirable. It is also desirable to use a compound in which the proportion of cyclic structures in such an active hydrogen group-containing organic compound, in other words the content ratio in one molecule, is generally 15% by mass or more, preferably 25% by mass or more, and more preferably 35% by mass or more. Furthermore, it is desirable for such an active hydrogen group-containing organic compound to be a bifunctional or higher functional compound, and in addition, it is desirable for the molecular weight to be within the range of 50 to 10,000, preferably 80 to 5,000, and more preferably 100 to 3,000. This makes it possible to achieve the object of the present invention even more advantageously.

[0022] The active hydrogen group-containing organic compound having such a cyclic structure is not particularly limited, and may be appropriately selected from various known compounds, such as phenols, alcohols, amines, and thiols, each having an aromatic cyclic, alicyclic, or heterocyclic structure.

[0023] Specifically, phenolic compounds include low molecular weight phenolic compounds such as phenol, cresol, xylenol, hydroquinone, catechol, resorcinol, pyrogallol, phloroglucinol, alkylhydroquinone, dialkylhydroquinone, trialkylhydroquinone, tetraalkylhydroquinone, and dihydroxynaphthalene, and high molecular weight phenolic compounds such as bisphenol A, bisphenol F, novolac-type phenolic resins, resol-type phenolic resins, and benzylic ether-type phenolic resins obtained by reacting phenolic compounds such as phenol and cresol with aldehydes and ketones; aromatic alcohols such as benzyl alcohol, methylbenzyl alcohol, phenethyl alcohol, hydroxybenzyl alcohol, hydroxyphenethyl alcohol, methoxyphenylmethanol, benzenedimethanol, benzenediethanol, and 1,4-bis(α-hydroxyisopropyl)benzene; and aniline, phenylenediamine, tolylenediamine, xylylenediamine, and toluenediamine having primary and / or secondary amino groups. aromatic amines such as methylenedianiline, diaminodiphenyl ether, trimethylphenylenediamine, diethyltoluenediamine, dimethylthiotoluenediamine, N,N'-bis(sec-butylamino)diphenylmethane, aminobenzylamine, methylenebis(ethylmethylaniline), and methylenebis(diethylaniline); alicyclic alcohols such as cyclohexanol, methylcyclohexanol, dimethylcyclohexanol, cyclohexanemethanol, cyclohexaneethanol, cyclobutanediol, cyclopentanediol, cyclohexanediol, cycloheptanediol, cyclooctanediol, hydroxypropylcyclohexanol, dicyclohexanediol, butylcyclohexanediol, cyclohexanedimethanol, cyclohexanediethanol, and inositol; alicyclic amines such as cyclohexanediamine, norbornenediamine, isophoronediamine, bis(aminomethyl)norbornane, bis(4-aminocyclohexyl)methane, diaminodicyclohexylmethane, and bisaminomethylcyclohexane;Examples of the polyols include heterocyclic compounds such as dihydroxypyridine, sucrose, glucoside, melamine, sorbitan, and sorbitan monolaurate; polyols obtained by reacting hydroxyl group-containing compounds having a cyclic structure or primary or secondary amines with alkylene oxides, such as polyether polyols which are reaction products obtained by reacting ethylene oxide or propylene oxide with phenolic compounds, phenolic resins, aromatic alcohols, cyclic sugars, or the like as initiators;

[0024] In the present invention, among the above-mentioned active hydrogen group-containing organic compounds, various phenolic compounds including low molecular weight and high molecular weight phenolic compounds are advantageously used, and among them, phenolic resins in particular are advantageously used because they have a high density of aromatic rings, which are cyclic structures, and thus the solidified body formed is difficult to burn and easy to obtain high strength.Furthermore, as such phenolic resins, those having a weight average molecular weight generally within the range of 200 to 10,000, 300 to 5,000, or 400 to 3,000 are preferably used.

[0025] In addition, a catalyst is further used as another essential component in the A solution constituting the present invention, and in the present invention, a metal carboxylate is used as at least one of such catalysts. By using such a metal carboxylate, it is possible to increase the reaction rate of the reaction between the above-mentioned active hydrogen group-containing organic compound and the aliphatic polyisocyanate compound to a practically suitable rate. Here, the metal carboxylate, which is an essential component as one of the catalysts in the present invention, is a compound in which hydrogen in the carboxyl group of an organic carboxylic acid is replaced with a metal such as tin, lead, zinc, iron, copper, nickel, cobalt, manganese, zirconium, or bismuth, and specific examples thereof include tin carboxylate, lead carboxylate, zinc carboxylate, iron carboxylate, copper carboxylate, nickel carboxylate, cobalt carboxylate, manganese carboxylate, zirconium carboxylate, and bismuth carboxylate.

[0026] Among these metal carboxylates, more specific examples of tin carboxylates include tin acetate, tin butyrate, tin octylate, tin naphthenate, tin oleate, tin laurate, stannous octanoate, stannous dilaurate, stannous dipalmitate, stannous distearate, stannous dioleate, tin bis(neodecanoate), tin stearate, tin benzoate, etc. Examples of lead carboxylates include lead acetate, lead butyrate, lead octylate, lead naphthenate, lead oleate, lead octanoate, lead neodecanoate, lead laurate, lead stearate, lead benzoate, etc. Examples of zinc carboxylates include zinc acetate, zinc butyrate, zinc octylate, zinc naphthenate, zinc oleate, zinc octanoate, zinc neodecanoate, zinc laurate, zinc stearate, zinc benzoate, etc.

[0027] In addition, examples of iron carboxylates include iron acetate, iron butyrate, iron octoate, iron naphthenate, iron oleate, iron octanoate, iron neodecanoate, iron laurate, iron stearate, and iron benzoate. Examples of copper carboxylates include copper acetate, copper butyrate, copper octoate, copper naphthenate, copper oleate, copper octanoate, copper neodecanoate, copper laurate, copper stearate, and copper benzoate. Further, examples of nickel carboxylates include nickel acetate, nickel butyrate, nickel octylate, nickel naphthenate, nickel oleate, nickel octanoate, nickel neodecanoate, nickel laurate, nickel stearate, and nickel benzoate. Examples of cobalt carboxylates include cobalt acetate, cobalt butyrate, cobalt octylate, cobalt naphthenate, cobalt oleate, cobalt octanoate, cobalt neodecanoate, cobalt laurate, cobalt stearate, and cobalt benzoate.

[0028] Furthermore, examples of manganese carboxylates include manganese acetate, manganese butyrate, manganese octylate, manganese naphthenate, manganese oleate, manganese octanoate, manganese neodecanoate, manganese laurate, manganese stearate, manganese benzoate, etc. Examples of zirconium carboxylates include zirconium acetate, zirconium butyrate, zirconium octylate, zirconium naphthenate, zirconium oleate, zirconium octanoate, zirconium neodecanoate, zirconium laurate, zirconium stearate, zirconium benzoate, etc. Examples of bismuth carboxylates include bismuth acetate, bismuth butyrate, bismuth octylate, bismuth naphthenate, bismuth oleate, bismuth octanoate, bismuth neodecanoate, bismuth laurate, bismuth stearate, bismuth benzoate, etc.

[0029] In particular, in the present invention, among the many metal carboxylates mentioned above, bismuth carboxylate is advantageously used since it has characteristics such as a fast reaction rate and no toxicity.

[0030] The amount of the metal carboxylate used as one of such catalysts is generally selected within the range of about 0.1 to 10 parts by mass, preferably 0.3 to 5 parts by mass, relative to 100 parts by mass of the active hydrogen group-containing compound in Solution A, in order to effectively exert its catalytic function. If the amount of the metal carboxylate used is too small, there is a problem that the reaction rate between the active hydrogen group-containing compound and the polyisocyanate becomes too slow, while if the amount used is too large, there is a problem that the reaction rate becomes too fast.

[0031] In addition, the solution A according to the present invention may contain various other known catalysts, i.e., tertiary amine catalysts, quaternary ammonium salts, etc., as necessary, along with the above-mentioned carboxylate metal salts, but in the present invention, tertiary amine catalysts are particularly advantageously used. By using such a tertiary amine catalyst in combination, the reaction rate of the chemical composition according to the present invention is less affected even in the presence of water. Therefore, at the site where the chemical composition according to the present invention is injected, the difference in reaction time between when there is substantially no water and when there is water is small.

[0032] Here, the tertiary amine catalyst may be, in the case where foaming is intended upon contact with water, a foaming catalyst having the effect of promoting the reaction between a polyisocyanate and water, a resinification catalyst having the effect of promoting the reaction between a polyisocyanate and a polyol, or an isocyanurate catalyst having the effect of promoting the trimerization of a polyisocyanate, and any of these may be appropriately selected from known catalysts.

[0033] Specifically, examples of the foaming catalyst include N,N,N',N",N"-pentamethyldiethylenetriamine, N,N,N'-triethylaminoethylethanolamine, bis(dimethylaminoethyl)ether, N,N,N'-trimethylaminoethylpiperazine, N,N-dimethylaminoethoxyethanol, and triethylamine. Examples of the resinification catalyst include N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethylpropanediamine, N,N,N',N'-tetramethylhexanediamine, triethylenediamine, 33% triethylenediamine·67% dipropylene glycol, N,N-dimethylaminohexanol, N,N-dimethylaminoethanol, N-methyl-N'-hydroxyethylpiperazine, N-methylmorpholine, 1-methylimidazole, and 1,2-dimethylimidazole. Further, examples of the isocyanurate catalyst include 2,4,6-tris(dimethylaminomethyl)phenol, N,N',N"-tris(dimethylaminopropyl)-hexahydro-s-triazine, and the like. These catalysts may be used alone or in combination of two or more. Among these, foaming catalysts or resinification catalysts are preferably used.

[0034] The amount of the tertiary amine catalyst contained in the A solution is generally determined to be 0.5 to 10 parts by mass, preferably 0.8 to 5 parts by mass, per 100 parts by mass of the active hydrogen group-containing compound. If the catalyst content is less than 0.5 parts by mass, the contribution to the reaction is reduced, and it is difficult to sufficiently contribute to improving the reaction rate in the presence of water. If the catalyst content is more than 10 parts by mass, the reaction becomes too fast, causing problems such as difficulty in controlling the reaction rate. Furthermore, when such a tertiary amine catalyst is used together with the above-mentioned carboxylate metal salt catalyst, the ratio (mass ratio) of carboxylate metal salt: tertiary amine is generally about 5:1 to 1:5, preferably about 3:1 to 1:3.

[0035] Examples of quaternary ammonium salts include aliphatic ammonium compounds such as tetramethylammonium, methyltriethylammonium, ethyltrimethylammonium, propyltrimethylammonium, butyltrimethylammonium, pentyltrimethylammonium, hexyltrimethylammonium, heptyltrimethylammonium, octyltrimethylammonium, nonyltrimethylammonium, decyltrimethylammonium, undecyltrimethylammonium, dodecyltrimethylammonium, tridecyltrimethylammonium, tetradecyltrimethylammonium, heptadecyltrimethylammonium, hexadecyltrimethylammonium, heptadecyltrimethylammonium, and octadecyltrimethylammonium; hydroxylammonium compounds such as (2-hydroxypropyl)trimethylammonium, hydroxyethyltrimethylammonium, and trimethylaminoethoxyethanol; and alicyclic ammonium compounds such as 1-methyl-1-azania-4-azabicyclo[2,2,2]octanium, 1,1-dimethyl-4-methylpiperidinium, 1-methylmorpholinium, and 1-methylpiperidinium. Among these, tetramethylammonium, methyltriethylammonium, ethyltrimethylammonium, butyltrimethylammonium, hexyltrimethylammonium, octyltrimethylammonium, decyltrimethylammonium, dodecyltrimethylammonium, tetradecyltrimethylammonium, hexadecyltrimethylammonium, octadecyltrimethylammonium, (2-hydroxypropyl)trimethylammonium, hydroxyethyltrimethylammonium, 1-methyl-1-azania-4-azabicyclo[2,2,2]octanium, and 1,1-dimethyl-4-methylpiperidinium are preferably used because they have excellent catalytic activity and are industrially available.

[0036] Examples of organic acid groups or inorganic acid groups constituting such quaternary ammonium salts include organic acid groups such as formic acid group, acetic acid group, octylic acid group, oxalic acid group, malonic acid group, succinic acid group, glutaric acid group, adipic acid group, benzoic acid group, toluic acid group, ethylbenzoic acid group, methylcarbonate group, phenol group, alkylbenzenesulfonic acid group, toluenesulfonic acid group, benzenesulfonic acid group, and phosphate ester group, and inorganic acid groups such as halogen group, hydroxyl group, hydrogencarbonate group, and carbonate group. Among these, formic acid group, acetic acid group, octylic acid group, methylcarbonate group, halogen group, hydroxyl group, hydrogencarbonate group, and carbonate group are preferred because of their excellent catalytic activity and industrial availability.

[0037] On the other hand, as for the polyisocyanate, which is an essential component of liquid B, the other of the two liquids constituting the liquid ground consolidation composition that is the subject of the present invention, in the present invention, not only an aliphatic polyisocyanate compound itself is used, but also a prepolymer (aliphatic polyisocyanate prepolymer) derived from such an aliphatic polyisocyanate compound is advantageously used.

[0038] Examples of the aliphatic polyisocyanate compound include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, dimer acid diisocyanate, methyl 2,6-diisocyanatohexanoate (lysine diisocyanate), aliphatic diisocyanates such as 2,6-diisocyanatohexanoate, 2-isocyanatoethyl 2,6-diisocyanatohexanoate, 1,6-diisocyanato-3-isocyanatomethylhexane, 1,4,8-triisocyanatooctane, 1,6,11-triisocyanatoundecane, 1,8-diisocyanato-4-isocyanatomethyloctane, 1,3,6-triisocyanatohexane, 2,5,7-trimethyl-1,8-diisocyanato-5-isocyanatomethyloctane, and other aliphatic polyisocyanates. diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (isophorone diisocyanate), 4-methyl-1,3-cyclohexylene diisocyanate (hydrogenated TDI), 2-methyl-1,3-cyclohexylene diisocyanate, 1,3- or 1,4-bis(isocyanatomethyl)cyclohexane (hydrogenated xylylene diisocyanate) or mixtures thereof, methylene bis(4,1-cyclohexa Alicyclic diisocyanates such as norbornane diisocyanate (hydrogenated MDI), 1,3,5-triisocyanatocyclohexane, 1,3,5-trimethylisocyanatocyclohexane, 2-(3-isocyanatopropyl)-2,5-di(isocyanatomethyl)-bicyclo(2,2,1)heptane, 2-(3-isocyanatopropyl)-2,6-di(isocyanatomethyl)-bicyclo(2,2,1)heptane, 3-(3-isocyanatopropyl)-2,5-di(isocyanatomethyl)-bicyclo(2,2,1) Heptane, 5-(2-isocyanatoethyl)-2-isocyanatomethyl-3-(3-isocyanatopropyl)-bicyclo(2,2,1)heptane, 6-(2-isocyanatoethyl)-2-isocyanatomethyl-3-(3-isocyanatopropyl)-bicyclo(2,2,1)heptane, 5-(2-isocyanatoethyl)-2-isocyanatomethyl-2-(3-isocyanatopropyl)-bicyclo(2,2,1)heptane, 6-(2-isocyanatoethyl)-2-isocyanatomethyl-2-(3-isocyanatopropyl)-bicyclo(2 ,2,1) alicyclic polyisocyanates such as alicyclic triisocyanates such as heptane; 1,3- or 1,4-xylylene diisocyanate or a mixture thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene (tetramethylxylylene diisocyanate) or a mixture thereof, and araliphatic diisocyanates such as 1,3,5-triisocyanatomethylbenzene and other araliphatic triisocyanates.

[0039] The aliphatic polyisocyanate prepolymer is not particularly limited, but for example, an adduct, biuret, or allophanate obtained by reacting the above-mentioned aliphatic polyisocyanate compounds such as pentamethylene diisocyanate, hexamethylene diisocyanate, octamethylene diisocyanate, bis(isocyanatomethyl)cyclohexane, or isophorone diisocyanate with an active hydrogen group-containing compound, or an isocyanurate obtained by trimerizing such a polyisocyanate compound, is preferably used. Note that there is no problem even if the isocyanurate contains a dimer uretdione. In addition, in consideration of the properties such as the strength and flame retardancy of the solidified body, an isocyanurate is more preferably used for such an aliphatic polyisocyanate prepolymer.

[0040] Furthermore, since such an aliphatic polyisocyanate prepolymer is obtained by modifying the above-mentioned aliphatic polyisocyanate compound, the raw material aliphatic polyisocyanate compound remains as an unreacted monomer component in the prepolymer, which is the modified product, but in the present invention, such residual monomer components are preferably 5% by mass or less, and in particular, the prepolymer of the aliphatic polyisocyanate compound is prepared so that it is 1% by mass or less. If the amount of such residual monomer components increases, it will cause a decrease in physical properties such as the strength of the solidified body, and will also cause problems such as the monomer components volatilizing during construction, worsening the working environment.

[0041] The aliphatic polyisocyanate compound or its prepolymer as described above is generally contained in the B liquid at a ratio of 50 to 100% by mass, preferably 70 to 100% by mass, more preferably 80 to 100% by mass. If the content of the aliphatic polyisocyanate compound or its prepolymer is less than 50% by mass, there is a problem that the strength of the solidified body decreases, so that the ratio of the aliphatic polyisocyanate compound or its prepolymer in the B liquid is preferably high, and it is also possible to constitute the B liquid only with such an aliphatic polyisocyanate compound or its prepolymer. It is also possible to contain a known aromatic polyisocyanate in the B liquid within a range not exceeding 10% by mass.

[0042] Incidentally, the above-mentioned A liquid and B liquid consolidating the ground liquid according to the present invention can be added with additives similar to those used in the past, depending on the purpose of use. For example, additives for A liquid can include foaming agents, foam stabilizers, flame retardants, viscosity reducers, etc. These additives for A liquid are generally used appropriately in a ratio of about 0.1 to 50 parts by mass, preferably about 0.5 to 40 parts by mass, per 100 parts by mass of the active hydrogen group-containing organic compound. Examples of additives for the B liquid include foam stabilizers, flame retardants, viscosity reducers, etc., and among these, the foam stabilizer is used in an amount of 0.05 to 5 parts by mass, and preferably 0.1 to 3 parts by mass, per 100 parts by mass of the polyisocyanate component, the viscosity reducer is used in an amount of 0.5 to 60 parts by mass, and preferably 1 to 40 parts by mass, per 100 parts by mass of the polyisocyanate component, and the flame retardant is used in an amount of 1 to 50 parts by mass, and preferably 5 to 40 parts by mass, per 100 parts by mass of the polyisocyanate component.

[0043] Among these additives, the foaming agent may be any of the known additives such as water, hydrocarbons, hydrofluorocarbons, hydrofluoroolefins, and hydrochlorofluoroolefins. The foaming agent is not particularly limited, but water is preferably used. This water is also supplied from the ground to which the chemical composition is applied, and reacts with the polyisocyanate of the B liquid to generate carbon dioxide gas, so that it functions as a foaming agent.

[0044] The foam stabilizer is used to uniformly adjust the cell structure of the foam formed by the reaction of the A liquid and the B liquid. Examples of the foam stabilizer include silicone, nonionic surfactants, polyoxyalkylene-modified dimethylpolysiloxane, polysiloxane oxyalkylene copolymer, polyoxyethylene sorbitan fatty acid ester, castor oil ethylene oxide adduct, lauryl fatty acid ethylene oxide adduct, etc., and among these, silicone and nonionic surfactants are preferably used. These may be used alone or in combination of two or more. Among the foam stabilizers, silicone-based foam stabilizers are more preferable, and polyoxyalkylene-modified dimethylpolysiloxane, polysiloxane oxyalkylene copolymer, etc. are preferable.

[0045] Furthermore, as the flame retardant, a liquid flame retardant or a powder flame retardant can be used. These flame retardants can be dispersed and contained in either Liquid A or Liquid B. These flame retardants may be used alone or in combination of two or more. In particular, it is preferable to use a liquid flame retardant because it also functions as a viscosity reducer for the foamable composition. Furthermore, by using a liquid flame retardant and a powder flame retardant in combination, the flame retardancy can be further improved.

[0046] Examples of liquid flame retardants include phosphate esters and bromine-containing flame retardants, and phosphate esters are preferably used because they have a low environmental impact. Examples of phosphate esters include monophosphate esters and condensed phosphate esters.

[0047] Examples of monophosphate esters include trimethyl phosphate, triethyl phosphate, tributyl phosphate, tri(2-ethylhexyl) phosphate, tributoxyethyl phosphate, triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, tris(isopropylphenyl) phosphate, tris(phenylphenyl) phosphate, trinaphthyl phosphate, cresyl diphenyl phosphate, xylenyl diphenyl phosphate, diphenyl(2-ethylhexyl) phosphate, di(isopropylphenyl)phenyl phosphate, monoisodecyl phosphate, 2-acryloyl phosphate, Examples of the acryloyloxyethyl phosphate include 2-methacryloyloxyethyl acid phosphate, diphenyl-2-acryloyloxyethyl phosphate, diphenyl-2-methacryloyloxyethyl phosphate, melamine phosphate, dimelamine phosphate, melamine pyrophosphate, triphenylphosphine oxide, tricresylphosphine oxide, diphenyl methanephosphonate, diethyl phenylphosphonate, resylcinol bis(diphenyl phosphate), bisphenol A bis(diphenyl phosphate), phosphaphenanthrene, and tris(β-chloropropyl)phosphate.

[0048] Further, examples of the condensed phosphate ester include trialkyl polyphosphate, resorcinol polyphenyl phosphate, resorcinol poly(di-2,6-xylyl) phosphate (manufactured by Daihachi Chemical Industry Co., Ltd., trade name: PX-200), hydroquinone poly(2,6-xylyl) phosphate, and condensates thereof. Examples of commercially available condensed phosphate esters other than those mentioned above include resorcinol polyphenyl phosphate (trade name: CR-733S), bisphenol A polycresyl phosphate (trade name: CR-741), aromatic condensed phosphate ester (trade name: CR747), resorcinol polyphenyl phosphate (manufactured by ADEKA Corporation, trade name: Adekastab PFR), bisphenol A polycresyl phosphate (trade name: FP-600, FP-700), etc.

[0049] In addition, examples of bromine-containing flame retardants include monomeric organic bromine compounds such as hexabromobenzene, pentabromotoluene, hexabromobiphenyl, decabromobiphenyl, hexabromocyclodecane, decabromodiphenyl ether, octabromodiphenyl ether, hexabromodiphenyl ether, bis(pentabromophenoxy)ethane, ethylene-bis(tetrabromophthalimide), and tetrabromobisphenol A; brominated polycarbonates such as polycarbonate oligomers produced using brominated bisphenol A as a raw material, and copolymers of the polycarbonate oligomers and bisphenol A; brominated epoxy compounds such as diepoxy compounds produced by the reaction of brominated bisphenol A with epichlorohydrin, and monoepoxy compounds obtained by the reaction of brominated phenols with epichlorohydrin; poly(brominated benzyl acrylate); brominated polyphenylene ether; condensates of brominated bisphenol A, cyanuric chloride, and brominated phenol; brominated polystyrenes such as brominated (polystyrene), poly(brominated styrene), and crosslinked brominated polystyrene; and halogenated bromine compound polymers such as crosslinked or non-crosslinked brominated poly(methylstyrene).

[0050] Examples of powdered flame retardants include red phosphorus, phosphate-containing flame retardants, stannate-containing flame retardants, boron-containing flame retardants, metal hydroxides, metal oxides, etc., and red phosphorus, boron-containing flame retardants, and metal hydroxides are preferably used because of ease of handling. As the red phosphorus, known red phosphorus can be used.

[0051] In this regard, examples of the phosphate-containing flame retardant include phosphates such as monophosphates, pyrophosphates, polyphosphates, etc. Examples of the monophosphates include ammonium salts such as ammonium phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; sodium salts such as monosodium phosphate, disodium phosphate, trisodium phosphate, monosodium phosphite, disodium phosphite, and sodium hypophosphite; potassium salts such as monopotassium phosphate, dipotassium phosphate, tripotassium phosphate, monopotassium phosphite, dipotassium phosphite, and potassium hypophosphite; lithium salts such as monolithium phosphate, dilithium phosphate, trilithium phosphate, monolithium phosphite, dilithium phosphite, and lithium hypophosphite; barium salts such as barium dihydrogen phosphate, barium hydrogen phosphate, tribarium phosphate, and barium hypophosphite; magnesium salts such as monohydrogen magnesium phosphate, hydrogen magnesium phosphate, trimagnesium phosphate, and magnesium hypophosphite; calcium salts such as calcium dihydrogen phosphate, calcium hydrogen phosphate, tricalcium phosphate, and calcium hypophosphite; and zinc salts such as zinc phosphate, zinc phosphite, and zinc hypophosphite. Examples of polyphosphates include ammonium polyphosphate, piperazine polyphosphate, melamine polyphosphate, ammonium amide polyphosphate, and aluminum polyphosphate.

[0052] Examples of stannate-containing flame retardants include zinc stannate, barium stannate, sodium stannate, potassium stannate, cobalt stannate, and magnesium stannate.

[0053] Further, examples of the boron-containing flame retardant include borax, boron oxide, boric acid, borate salts, etc. Specific examples of boron oxide include diboron trioxide, boron trioxide, diboron dioxide, tetraboron trioxide, tetraboron pentoxide, etc. Further, examples of the borate salt include alkali metal borate salts such as lithium borate, sodium borate, potassium borate, cesium borate, etc.; alkaline earth metal borate salts such as magnesium borate, calcium borate, barium borate, etc.; zirconium borate, zinc borate, aluminum borate, ammonium borate, etc.

[0054] Examples of metal hydroxides include magnesium hydroxide, calcium hydroxide, aluminum hydroxide, iron hydroxide, nickel hydroxide, zirconium hydroxide, titanium hydroxide, zinc hydroxide, copper hydroxide, vanadium hydroxide, tin hydroxide, etc. In addition, examples of metal oxides include zinc oxide, aluminum oxide, titanium oxide, etc.

[0055] In addition, the viscosity reducer is used as a solvent, and is dissolved in liquid A or liquid B to reduce the viscosity of those liquids, and is not particularly limited as long as it has such a function, and examples thereof include alcohols such as methanol and ethanol, ethers such as ethyl cellosolve and butyl cellosolve, cyclic esters such as propylene carbonate, esters such as dicarboxylic acid methyl esters and ethylene glycol monomethyl ether acetate, petroleum hydrocarbons, etc. These may be used alone or in combination of two or more kinds.

[0056] Meanwhile, the A liquid and the B liquid prepared according to the present invention are adjusted so that their viscosities at a temperature of 25°C are 6000 mPa·s or less, preferably 10 to 5000 mPa·s, and more preferably 20 to 3500 mPa·s. If the viscosity is higher than 6000 mPa·s, the A liquid and the B liquid become viscous liquids, and the fluidity during mixing is poor, and the fluidity during pumping is also poor, which may cause problems such as an increase in injection pressure. If the viscosity is lower than 20 mPa·s, the A liquid and the B liquid are easily diluted with water, which may cause problems such as clouding of the wastewater. In addition, the A liquid and the B liquid may be adjusted in temperature using a heater to reduce the viscosity during pumping, and may be heated to 0 to 50°C depending on the outside air temperature.

[0057] In addition, when using the liquid composition for natural ground consolidation according to the present invention, which is composed of such liquid A and liquid B, the two liquids are mixed at the time of use, injected into the target natural ground, ground, rock, etc., according to a known method, and reacted and hardened to form a high-strength solidified body. The mixing ratio of liquid A and liquid B is appropriately changed depending on the total content (total number of moles: X) of active hydrogen groups (OH groups, NH2 groups) in liquid A that is introduced by the active hydrogen group-containing organic compound having a cyclic structure, and the content (number of moles: Y) of isocyanate groups (NCO groups) in liquid B that is introduced by polyisocyanate, but is generally adopted within the range of X / Y=0.3 to 3.0, preferably 0.3 to 2.8, and more preferably 0.4 to 2.4 in terms of molar ratio. If the molar ratio (X / Y) is less than 0.3, it becomes difficult to impart sufficient strength to the solidified body formed, and there is a risk that the natural ground cannot be sufficiently improved. On the other hand, if the molar ratio is more than 3.0, the reaction does not proceed sufficiently, and the strength and flexibility of the solidified body may be insufficient.

[0058] Thus, when mixing the liquids A and B according to the present invention, the mixing ratio (A:B) is appropriately determined while taking into consideration the active hydrogen group content in the liquid A and the isocyanate group content in the liquid B, and generally, a ratio of A:B=2:1 to 1:3, preferably 1:1 to 1:2, is adopted on a mass basis. The method of using the liquids A and B is also not particularly limited as long as it is a method that can reliably mix the two liquids immediately before use, and various conventionally known injection methods are appropriately adopted.

[0059] Furthermore, the reaction time (time from mixing to hardening) when liquid A and liquid B are mixed is preferably within 600 seconds, more preferably 20 to 360 seconds, when the liquid temperature is 25°C. If the reaction time is longer than 600 seconds, problems such as the liquid flowing out into the spring water after injection into the natural ground and before solidification, causing water to become cloudy or foaming, etc. If the reaction time is too short, for example, shorter than 20 seconds, the reaction proceeds too quickly, causing problems such as clogging the injection pipe of the liquid and making it difficult to sufficiently penetrate the natural ground. EXAMPLES

[0060] The present invention will be clarified in more detail by showing some examples and comparative examples below, but it goes without saying that the present invention is not limited in any way by the description of such examples. It should be understood that the present invention can be modified, revised, improved, etc., based on the knowledge of a person skilled in the art, in addition to the following examples and the above specific description, without departing from the spirit of the present invention.

[0061] In the following Examples and Comparative Examples, the properties (viscosity) of Liquid A and Liquid B obtained, as well as the mixability of Liquid A and Liquid B when they are mixed, the degree of cloudiness of water after Liquid A and Liquid B are reacted and foamed in water, the reaction time when Liquid A and Liquid B are mixed and reacted and hardened, the compressive strength and flexural strength of the reaction product, the foaming ratio in the presence / absence of water, and the oxygen index of the reaction product were each measured or evaluated according to the following methods. Also, the "%", "ratio" and "parts" shown below are all based on mass.

[0062] (1) Viscosity measurement The viscosities of the liquids A and B obtained in the examples and comparative examples were measured using a Brookfield type viscometer in accordance with JIS-K-7117-1:1999.

[0063] (2) Evaluation of compatibility Liquid A and liquid B adjusted to a temperature of 25°C were placed in a 300 ml cup at a mixing ratio specified in each Example and Comparative Example to make a total of 100 parts, and immediately mixed with a spatula for 20 seconds, and the state of the mixture was observed from the start of mixing to after mixing. The mixture was then evaluated as follows: ◯ if liquid A and liquid B were sufficiently mixed after 20 seconds had elapsed, △ if the mixture was slightly insufficient due to thickening during mixing, and × if the mixture was not sufficient due to thickening during mixing and there was unevenness in the solidified product.

[0064] (3) Evaluation of cloudiness The A liquid and the B liquid, which were adjusted to a temperature of 25°C, were weighed and mixed in a total amount of 100 ml at the mixing ratio adopted in each Example and Comparative Example. Then, immediately after the mixing, the mixture of the A liquid and the B liquid was poured into 1 L of water at 25°C contained in a 2 L disc cup, and left to stand until the reaction subsided. After the reaction was completed, the state of the water was visually observed, and the evaluation was performed as follows: ○ if no turbidity was observed immediately after the reaction subsided, △ if turbidity was not observed within 1 hour after the reaction subsided, and × if turbidity was observed even after 1 hour or more had passed after the reaction subsided.

[0065] (4) Measurement of reaction time Liquid A and liquid B, adjusted to a temperature of 25°C, were mixed in the mixing ratio employed in each Example and Comparative Example to initiate the reaction. The reaction time was then determined as the time until gas was generated from the reaction product and the foam height no longer changed, or the time until a skewer could no longer be pierced into the reaction product, whichever was later.

[0066] (5) Compressive strength test / flexural strength test Liquid A and liquid B adjusted to a temperature of 25°C were weighed and mixed in a total amount of 100 ml at the mixing ratio adopted in each Example and Comparative Example. Then, immediately after such mixing, a predetermined amount of the mixture of liquid A and liquid B was poured into a bottomed cylindrical mold with an inner diameter of 50 mm and a height of 100 mm, and after closing the lid, curing was carried out for 2 hours or more. Thereafter, the reaction product was demolded and cured at a temperature of 25°C for 24 hours or more, and the compressive strength was measured in accordance with JIS-K-7220:2006.

[0067] The bending strength was measured in accordance with JIS-K-7221:2006 using test specimens made of the reaction products obtained in the same manner as above.

[0068] (6) Measurement of foaming ratio Liquid A and liquid B adjusted to a temperature of 25°C were weighed out in the mixing ratio adopted in each Example and Comparative Example so that the total amount was 100 ml, and these were placed in a 2 L disc cup and thoroughly mixed and stirred to harden. Then, the foam height of the reaction product after the hardening reaction was measured to obtain the foaming ratio.

[0069] (7) Measurement of reaction time and foaming ratio in the presence of water To the A solution in each of the Examples and Comparative Examples, 0.5 parts of a foam stabilizer: B8450 (manufactured by Evonik) and 2 parts of water were further added, and the reaction time and the expansion ratio in the presence of water were determined in the same manner as in (4) Measurement of reaction time and (6) Measurement of expansion ratio.

[0070] (8) Oxygen index (flame retardancy) evaluation In each Example and Comparative Example, 0.5 parts of foam stabilizer B8450 (manufactured by Evonik) and 2 parts of water were further added to the A liquid adjusted to a temperature of 25°C in each Example and Comparative Example, and the B liquid adjusted to a temperature of 25°C was mixed with this in the ratio adopted in each Example and Comparative Example, and immediately poured into a 250mm x 100mm x 50mm mold in an amount that would result in 3 times the foaming, and then, after covering, curing for 2 hours or more. After that, the mold was removed and cured at 25°C for 24 hours or more, and test specimens were cut out from the obtained reaction product, and the oxygen index of each test specimen was measured in accordance with JIS-K-7201-2:2007. Note that the larger the oxygen index, the better the flame retardancy.

[0071] First, the following various raw materials were prepared as components of the liquid A or liquid B used in the following examples and comparative examples. Polyol: Phenolic resin (prepared according to the synthesis method below) Resorcinol (Tokyo Chemical Industry Co., Ltd., aromatic ring content: 69%) PF300 [Asahi Organic Chemicals Co., Ltd., phenolic resin polyol (EOPO adduct), aromatic ring content: 46%] Cyclohexanedimethanol (Sanyo Chemical Industries, Ltd., 1,4-cyclohexanedimethanol, alicyclic content: 57%) : Sorbitan monolaurate (Fujifilm Wako Pure Chemical Industries, Ltd., Sorbitan monolaurate, heterocyclic content: 20%) : PP-400 [Sanyo Chemical Industries, Ltd., Sannics PP-2000 ( Polyether polyol, molecular weight 400, functional group 2), no cyclic structure : 450ED [AGC Corporation, Excelol 450ED (polyether polyol, molecular weight 400, functional group number 4), no cyclic structure] Polyamine: Diethyltoluenediamine (Albemarle, Ethacure 100, aromatic ring content: 41%) Catalyst: Bismuth catalyst (manufactured by Nippon Chemical Industry Co., Ltd., bismuth octylate, bismuth concentration: 2.5%) : Tin catalyst (Nihon Kagaku Sangyo Co., Ltd., dibutyltin dioctate) : Kao Raiser No. 26 (Kao Corporation, tertiary amine catalyst) : Kao Raiser No. 390 (Kao Corporation, tertiary amine catalyst) Viscosity reducer: PC (Tokyo Chemical Industry Co., Ltd., propylene carbonate) : DOP (Tokyo Chemical Industry Co., Ltd., dioctyl phthalate) Flame retardant: Phosphate ester (Daihachi Chemical Industry Co., Ltd., tris(chloropropyl)phosphate) : Red phosphorus (Nova Excel 140, manufactured by Rinkagaku Kogyo Co., Ltd.) : Phosphinic acid salt (Clariant Chemicals, EXOLIT OP-935) : Aluminum hydroxide (Nippon Light Metal Co., Ltd., Aluminum hydroxide) Polyisocyanates : HDI Nurate (Mitsui Chemicals, Takenate D-170N, hexamethylene diisocyanate prepolymer, nurate type, NCO ratio: 21%) : HDI Biuret (Mitsui Chemicals, Takenate D-165N, hexamethylene diisocyanate prepolymer, biuret type, NCO ratio: 23.5%) : PDI nurate (Mitsui Chemicals, Inc., Stabio D-476N, pentamethylene diamine prepolymer, nurate type / allophanate type mixture, NCO ratio: 23.5%) : XDI (Mitsui Chemicals, Takenate 500, xylylene diisocyanate, NCO ratio: 47%) : MDI (Kumho Mitsui Chemicals, Cosmonate M-200, polymeric MDI, NCO ratio: 31%)

[0072] -Synthesis of phenolic resin- In a three-necked reaction flask equipped with a reflux condenser, a thermometer, and a stirrer, 50 parts of phenol and 50 parts of orthocresol (phenol / orthocresol=50 / 50) were charged together with 51.9 parts of 92% paraformaldehyde and 0.15 parts of zinc naphthenate as a divalent metal salt, and the mixture was reacted at reflux temperature for 90 minutes. The mixture was then washed with 100 parts of water to remove the water layer, and then heated and concentrated to obtain a phenolic resin (orthocresol modified benzyl ether type phenolic resin) with a water content of 1% or less. The synthesized phenolic resin had a free phenol content of 1% or less and a formaldehyde content of 0.1% or less. The aromatic ring content was 65%.

[0073] (Examples 1 to 19) - Preparation of solution A - The various raw materials prepared above, i.e., active hydrogen group-containing organic compounds (polyols, polyamines), catalysts, viscosity reducers, and flame retardants, were uniformly mixed in the various combinations and mixing ratios shown in Tables 1 and 2 below to prepare various A liquid blended compositions according to Examples 1 to 20. The viscosities of the obtained A liquid blended compositions were then measured, and the results are shown in Tables 1 and 2 below.

[0074] - Preparation of solution B - Using each of the polyisocyanates prepared above, a liquid B blend composition consisting of 100% of each of them was prepared. The viscosity of each of the liquid B blend compositions obtained was then measured, and the results are shown in Tables 1 and 2 below.

[0075] -Reaction of solution A and solution B- The A and B solutions obtained above were combined in the ratios shown in Tables 1 and 2, and were uniformly mixed and reacted at room temperature. Various evaluation tests were then carried out according to the evaluation methods described above, and the results are shown in Tables 1 and 2 below.

[0076] Comparative Example 1 The tests were carried out in the same manner as in Example 2, except that no bismuth catalyst was added as the catalyst in Example 2. The results are shown in Table 2 below.

[0077] Comparative Example 2 Tests were carried out in the same manner as in Example 2, except that a polyether polyol (450ED) not having a cyclic structure was used instead of the phenol resin in Example 2. The results are shown in Table 2 below.

[0078] Comparative Example 3 Tests were carried out in the same manner as in Example 2, except that MDI, which is not an aliphatic polyisocyanate compound but an aromatic polyisocyanate, was used instead of HDI nurate used as the polyisocyanate component in Example 2. The results are shown in Table 2 below.

[0079] [Table 1]

[0080] [Table 2]

[0081] As is clear from the results in Tables 1 and 2, in Examples 1 to 20, the liquid chemical compositions consisting of Liquid A and Liquid B according to the present invention all had excellent reaction activity with a reaction time of 600 seconds or less, had good mixability, and were capable of forming a solidified body with high compressive strength and excellent flexural strength, and also showed good results in the cloudiness test.

[0082] In contrast, among the liquid chemical compositions prepared in Comparative Examples 1 to 3 and consisting of Liquid A and Liquid B, the liquid chemical composition according to Comparative Example 1 was found to take a long time for the hardening reaction, to have poor reactivity, and to have poor compressive strength and bending strength of the solidified body. The liquid chemical composition according to Comparative Example 2 was found to be poor in the cloudiness test, and the liquid chemical composition according to Comparative Example 3 was found to have poor mixability, and to have poor compressive strength and bending strength of the solidified body obtained.

[0083] -Changes in reaction time and foaming ratio in the presence of water- Using the liquid chemical compositions prepared in Examples 1, 5-7, 11, 16-17, and Comparative Examples 1-3, 0.5 parts of a foam stabilizer: B8450 (manufactured by Evonik) and 2 parts of water were further added to each of the liquid A components, and the components were mixed with liquid B to react, and the reaction time and expansion ratio were investigated, and the results are shown in Table 3 below. For reference, the results shown in Tables 1 and 2 obtained by reacting liquid A with liquid B in the absence of water are shown in Table 4 as the reaction time and expansion ratio in the absence of water.

[0084] [Table 3]

[0085] As is clear from the results in Table 3, in the liquid chemical compositions of the respective Examples according to the present invention, the rate of change (times) of the reaction time in the presence of water relative to the reaction time in the absence of water is small, which indicates that the reaction between Liquid A and Liquid B is less susceptible to the effects of water. In contrast, in Comparative Examples 2 and 3, the rate of change of the reaction time in the presence of water is large, which indicates that the reaction between Liquid A and Liquid B is significantly affected by water.

[0086] - Examination of flame retardancy based on oxygen index - The oxygen index of each of the foamed products (solidified bodies) obtained by foaming and curing using the A liquid and the B liquid prepared in Examples 4 to 8, Examples 21 to 23, and Comparative Example 2 was measured, and the results are shown in Table 4 below.

[0087] [Table 4]

[0088] As is clear from the results in Table 4, the liquid chemical compositions of Examples 4 to 8 and Examples 21 to 23, which are composed of Liquid A and Liquid B according to the present invention, have oxygen indexes larger than that of the foamed solid obtained from the liquid chemical composition of Comparative Example 2, and it was thus recognized that these compositions give foamed solids with good flame retardancy.

Claims

[Claim 1] A liquid composition for natural ground consolidation comprising liquid A containing an active hydrogen group-containing compound and a catalyst as essential components, and liquid B containing a polyisocyanate as an essential component, A liquid composition for consolidating ground, characterized in that the A liquid contains at least an active hydrogen group-containing organic compound having a cyclic structure as the active hydrogen group-containing compound, and at least a carboxylic acid metal salt as the catalyst, and the B liquid contains at least an aliphatic polyisocyanate compound as the polyisocyanate.

Citation Information

Patent Citations

  • Grouting composition for stabilizing soil, etc., and engineering method using same for stabilizing and reinforcing soil and preventing water from gushing

    JP1992283290A

  • Fluid agent for concretion of rock bed

    JP1993078667A

  • Chemical for natural ground consolidation

    JP2016175982A